Development of strategies to support the resuscitation team in emergency departments of Mankweng and Pietersburg public hospitals in Limpopo Province, South Africa - Seimela, Mosima Hendrica (My University, 2022)
Background: Emergency departments (EDs) as the hospitals' front door have a critical role in ensuring access to and efficient care of acute illness and injuries in the healthcare system. The environment in EDs is physically and emotionally demanding and burdened by complex patient loads, long shifts, and administrative challenges resulting in high pressure and high volume workloads amongst the staff members. Purpose: The study aimed to develop support strategies for the resuscitation team in EDs of Mankweng and Pietersburg public hospitals in Limpopo Province, South Africa. Study method: A descriptive, phenomenological, and explorative research design was used to explore the resuscitation team's experiences and the available strategies to support them. Purposive and convenience sampling methods were used to select five Medical doctors and twelve Professional nurses to participate in the study. The sample size was determined by the depth of the information obtained from the participants.Data was collected through semi-structured individual interviews. Interview guide was developed to guide with organised line of questioning and thinking. Qualitative data analysis using Tesch's approach was then followed. The quality of data was ensured by applying four elements; credibility, transferability, dependability, and confirmability. Turfloop Research Ethics Committee, the Limpopo Department of Health, and the Mankweng/Pietersburg Ethics Committee permitted the study. The study's details were explained to potential participants, who then agreed to be part of the study and signed consent forms. Results: The following themes emerged: Challenges related to the shortage of resources in the ED, challenges related to lack of standardized procedures and policies for handling the resuscitation process, psychological challenges of resuscitation failure, leadership, and managerial support challenges, and challenges related to education and training of the resuscitation team. Conclusion: This study's results indicated that the resuscitation teams of EDs from Mankweng and Pietersburg Public Hospitals face challenges that cause them stress and burnout. The challenges result from an increased overload of work with no personnel and material resources. They become demoralized by being engaged in failed resuscitation with no psychological support from the management. They don't receive any debriefing or counseling post failed resuscitation and no educational backing of the management. The study's findings guided the researcher in developing strategies to support the resuscitation teams in the EDs of Mankweng and Pietersburg Public Hospitals.
Thesis (M. Nursing) -- University of Limpopo, 2022
Keywords: Strategies; Resuscitation team; Professional nurses; Medical doctors; Emergency medical services; Ambulances; Public hospitals -- Law and legislation; Ambulance service; Emergency medical personnel; Nurses -- Job stress